Penguatan Iman Kepada Allah Swt Sebagai Pembentukan Karakter Remaja di SMP Swasta Kesatria Medan - Indah Widya Jaya Putri Nasution; Fahrur Rozy; Sapri (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Education has spread widely to all corners of the country, but there are still students whose character is not good and not in accordance with Islamic character. Especially during adolescence, because adolescence is a transition period from childhood to adulthood, where children's hormones are not yet stable so they are easily influenced by surrounding conditions which results in the formation of bad character. Therefore, the aim of this research is to find out and provide answers to whether strengthening faith in Allah SWT can form good character. Because getting closer to Allah SWT should be able to form good character. This research uses qualitative research, data collection was carried out by interviews at the Medan Kesatria Private Middle School. The results of this research are that the formation of good children's character is caused by the habit of cultivating religious values ​​which are carried out every day, where these activities bring children closer to Allah SWT in accordance with the first pillar of faith, namely faith in Allah SWT, because by drawing closer to Allah SWT children will be afraid of doing bad deeds so that good character can be embedded in their souls.